Fiduciary Security Arrangements and Issues in Indonesia - M. Jamil (Lembaga Contrarius Indonesia, 2021)
In this paper, the author explores the law of fiduciary security. Fiduciary guarantees have been used in Indonesia since the Dutch colonial era as a form of guarantee born of jurisprudence. This form of guarantee is widely used in lending and borrowing transactions because the loading process is considered simple, easy, and fast, but it does not guarantee legal certainty. Before the Fiduciary Guarantee Act, in general, Fiduciary guarantees were regulated in Oogstverband (Staatsblad 1886 Number 57) and jurisprudence based on the Hooggerechtsh of (HGH) decision dated August 18, 1932. In 1999 the Fiduciary Guarantee Law was born (UU No. 42/ 1999). The research method used in this paper is a juridical-normative research method with a conceptual approach and a statutory approach.Keywords: Fiduciary; Security; Guarantee.